Synergistic application of Pseudomonas strains and compost mitigates lead (Pb) stress in sunflower (Helianthus annuus L.) via improved nutrient uptake, antioxidant defense and physiology - Aqsa Ayub; Muhammad Shabaan; Mehreen Malik; Hafiz Naeem Asghar; Usman Zulfiqar; Mukkaram Ejaz; Khaloud Mohammed Alarjani; Dunia A. Al Farraj (Ecotoxicology and Environmental Safety, 2024)
Lead (Pb) is one of the most dreadful non-essential elements whose toxicity has been well reported worldwide due to its interference with the major plant functions and its overall yield. Bioremediation techniques comprising the application of beneficial microorganisms have gained attention in recent times owing to their ecofriendly nature. Addition of organic matter to soil has been reported to stimulate microbial activities. Compost application improves soil structure and binds toxic contaminants due to its larger surface area and presence of functional groups. Furthermore, it stimulates soil microbial activities by acting as C-source. So, in current study, we investigated the individual and synergistic potential of two lead (Pb)-tolerant Pseudomonas strains alongwith compost (1% w/w) in sustaining sunflower growth under Pb contaminated soil conditions. Lead chloride (PbCl2) salt was used for raising desired Pb concentration (500 mg kg−1). Results revealed that Pb stress drastically affected all the measured attributes of sunflower plant, however joint application of rhizobacteria and compost counteracted these adverse effects. Among them, co-application of str-1 and compost proved to be significantly better than str-2, as its inoculation significantly improved shoot and root lengths (64 and 76%), leaf area and leaves plant−1 (95 and 166%), 100-achene weight (200%), no. of flowers plant−1 (138%), chl ‘a’, ‘b’ and carotenoid (86, 159 and 33%) contents in sunflower as compared to control treatments. Furthermore, inoculation of Pseudomonas fluorescens along with compost increased the NPK in achene (139, 200 and 165%), flavonoid and phenolic contents (258 and 185%) along with transpiration and photosynthetic rates (54 and 72%) in leaves as compared to control treatment under Pb contamination. In addition, Pb entry to roots, shoots and achene were significantly suppressed under by 87, 90 and 91% respectively due to integrated application of compost and str-1 as evident by maximum Pb-immobilization efficiency (97%) obtained in this treatment. Similarly, bioconcentration factors for roots, shoots and achene were found to be 0.58, 0.18 and 0.0055 with associated translocation factor (0.30), which also revealed phytostabilization of Pb under combined application of PGPR and compost. Since, phytoremediation of heavy metals under current scenario of increasing global population is inevitable, results of the current study concluded that tolerant PGPR species along with organic amendments such as compost can inhibit Pb uptake by sunflower and confer Pb tolerance via improved nutrient uptake, physiology, antioxidative defense and gas exchange.